Pengaruh Pengetahuan Pajak dan Tax Amnesty Terhadap Kepatuhan Wajib Pajak - Irsal Fauzi; Dewi Ari Ani (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
The importance of the role of taxes in development demands serious attention and efforts to ensure that the government has optimally collected taxes and distributed these tax revenues into development programs that improve welfare. The purpose of this study is to determine the effect of tax knowledge and tax amnesty on taxpayer compliance. The approach in this study uses quantitative methods, with sampling techniques using purposive sampling, as well as a sample of 100 respondents. The analysis technique uses multiple linear regression tests. The results showed that tax knowledge has a significant effect on taxpayer compliance and tax amnesty has a significant effect on taxpayer compliance.  This research has implications that the government should take policies and decisions to increase the role of tax amnesty and tax sanctions to overcome problems regarding non-compliance of taxpayers paying tax obligations and provide additional knowledge from other variables in increasing taxpayer compliance with paying taxes. The advice that can be submitted for further research is that you should use the method of direct interviews with respondents, so that more in-depth analysis results are obtained based on respondents' perspectives and perspectives on taxpayer compliance.